2019
DOI: 10.12998/wjcc.v7.i10.1093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perioperative transfusion in patients undergoing resection of colorectal cancer liver metastases: A population-based study

Abstract: BACKGROUND Perioperative allogeneic blood transfusion is associated with poorer outcomes. AIM To identify the factors that were associated with perioperative transfusion and to examine the impact of perioperative transfusion in patients undergoing resection of colorectal cancer (CRC) liver metastases. METHODS The United States National Inpatient Sample (NIS) database was searched for patients with CRC who received surgery for liver metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Moreover, a recent study could also demonstrate higher risks for postoperative morbidity depending on intraoperative transfusion requirements [ 30 ]. These findings are supported by a population-based study from the USA that reported increased risk for in-hospital mortality, morbidity and longer hospital stay [ 10 ]. A systematic review by Acheson et al recommended restrictive use of PRBC in surgeries of primary colorectal cancer (CRC) due to negative impacts on clinical parameters such as overall and cancer-related mortality [ 31 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, a recent study could also demonstrate higher risks for postoperative morbidity depending on intraoperative transfusion requirements [ 30 ]. These findings are supported by a population-based study from the USA that reported increased risk for in-hospital mortality, morbidity and longer hospital stay [ 10 ]. A systematic review by Acheson et al recommended restrictive use of PRBC in surgeries of primary colorectal cancer (CRC) due to negative impacts on clinical parameters such as overall and cancer-related mortality [ 31 ].…”
Section: Discussionsupporting
confidence: 61%
“…In fact, some centers report that up to one third of resected patients require blood transfusions with different extent [ 9 ]. Over the past years many studies have reported inferior OS in case of intensive intra- or postoperative transfusions of packed red blood cells (PRBC) [ 10 12 ]. Negative effects of blood transfusions have been described for various tumor entities such as esophageal cancer, hepatocellular carcinoma, non-small-cell lung cancer, and urothelial carcinoma [ 13 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Restrictive transfusion strategies can reduce the adverse prognosis of diseases and save the cost of national health resources compared with liberal transfusion strategies. Mortality of transfused patients has been demonstrated to be higher than that of non-transfused patients, other adverse events such as postoperative complications, myocardial infarction, congestive heart failure and respiratory complications are also at a higher risk [7,8]. At the same time, the economic burden on the state and patients caused by the waste of RBC resources should be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of the genome in human cells is transcribed into RNA molecules that lack protein-coding capacity (3,4). Of these, long non-coding RNAs (lncRNAs) are transcripts with lengths >200 nt (5) that play important roles in tumorigenesis and cancer progression (68). A growing number of gastric cancer-related lncRNAs have been identified in recent years.…”
Section: Introductionmentioning
confidence: 99%